Correlating key climate change variables and spread of Covid-19 pandemic in India- A critical review: Examining the relationship between climate change factors and the spread of Covid-19 in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
According to a visual study of globe maps, nations closer to the equator, where heat andhumidity are more common, have a lower prevalence of coronavirus illness 2019 (COVID-19). Manyvariables complicate the link between COVID-19 and climate, thus scientists are divided on how tointerpret this finding. It is important to compensate for characteristics such as air travel, automobileconcentration, urbanisation, COVID-19 testing intensity, cell phone use, income and old-age dependencyratio when calculating the logarithm of confirmed COVID-19 cases per million people in a nation. Casesper million people increased by 4.3 as of January 9, 2021, when a one-degree rise in absolute latitudewas taken into account. Our findings suggest that a nation that is 1000 kilometres closer to the equatorshould expect a 33 decrease in incidents per million people. It is reasonable to assume a 64 percentdifference in instances per million people between two hypothetical nations whose temperatures shift toa comparable level as two nearby seasons since the Earth's tilt toward the sun changes by 23.5 degreesbetween spring and fall. According to our findings, new cases of COVID-19 should decrease in thesummer and rise in the winter in most nations. However, our findings do not mean that the diseasewould disappear during the summer or that it will not afflict nations located close to the equator in thenear future. SARS-CoV-2 containment efforts may be aided rather than hindered by summer's highertemperatures and more intense UV radiation.